2020
DOI: 10.3390/foods9050648
|View full text |Cite
|
Sign up to set email alerts
|

Slaughter Characteristics of Feedlot-Finished Premium South African Lamb: Effects of Sex and Breed Type

Abstract: This study compared the carcass characteristics of ram and ewe lambs from South African wool, dual-purpose, meat, and fat-tailed sheep types, reared to produce premium lamb carcasses. The lambs were reared on a feedlot diet (10.41 MJ ME/kg feed and 19.06% crude protein) from weaning (30 kg live weight) until they attained a back-fat depth of ~4 mm, measured using ultrasound. After slaughter, the carcasses were assessed for retail cut yields, composition, and physical meat quality. Later, maturing lambs attaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…Research investigations of perceived sheepmeat eating quality sensory scores [ 28 ] and demographic influences [ 29 ] on Australian, American and Chinese consumers demonstrated a consistent consumer response to production factors of muscle type, sire, age, and sex. Evidence in the published literature [ 30 ] indicates that meat eating quality and fatty acid (FA) composition of lipids in tandem with variable fat deposition at the attainment of maturity, vary in the muscles of sheep due to differences in breed [ 31 , 32 , 33 , 34 ], physiological status, breeding systems [ 35 ], grass-fed versus concentrate feeding [ 36 , 37 ], and sex [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research investigations of perceived sheepmeat eating quality sensory scores [ 28 ] and demographic influences [ 29 ] on Australian, American and Chinese consumers demonstrated a consistent consumer response to production factors of muscle type, sire, age, and sex. Evidence in the published literature [ 30 ] indicates that meat eating quality and fatty acid (FA) composition of lipids in tandem with variable fat deposition at the attainment of maturity, vary in the muscles of sheep due to differences in breed [ 31 , 32 , 33 , 34 ], physiological status, breeding systems [ 35 ], grass-fed versus concentrate feeding [ 36 , 37 ], and sex [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“… Cloete et al (2012) reported no differences in cooking loss among diverse sheep breeds. Similarly, Van Der Merwe et al (2020) found that cooking loss did no differ between Dohne Merino, Dormer, Dorper, Meatmaster, Merino, Namaqua Afrikaner, and South African Mutton Merino. Watanabe et al (2018) concluded that drip loss is negatively correlated with pH, which may explain the differences in cooking loss between Dorper and DCC.…”
Section: Resultsmentioning
confidence: 84%
“…The SAMM breed is an efficient feed converter and does extremely well in feedlot and pasture systems because of its ability to utilize low-quality roughage [ 77 ], presenting favorable growth and meat production attributes even under intensive rearing conditions [ 78 ]. It is one of the most common feedlot breeds throughout South Africa [ 79 ], being one of the most heat-adapted wool breeds, with potential for breeding in the recommended regions of Pernambuco state.…”
Section: Resultsmentioning
confidence: 99%